The correlation between knowledge and nurse compliance in the use of personal protective equipment level 2 - Mardiansyah Mardiansyah; Rizka Febtrina; Sri Yanti; Dendy Kharisna (Palembang MediRose Publisher, 2022)
Background: Personal Protective Equipment (PPE) is divided into 3 levels, the use of which is adjusted to the location of health services due to the COVID-19 pandemic. The second level of PPE is intended for health workers who work in patient care rooms. One of the causes of high cases of nurses contracting viral infections is the lack of knowledge and compliance in using PPE. Purpose: The aim of this study was to find out the correlation between knowledge and nurse compliance in the use of PPE level 2. Methods: This study was a quantitative research with correlational analytic type. The number of respondents was 62 nurses. Collecting data using a knowledge (8 qoestions) and compliance (10 questions) questionnaire of nurses in the use of PPE level 2. The analysis used was univariate and bivariate analysis with the Pearson Product Moment test with level of significance at the alpha = 0.05. Results: The results of the univariate analysis of knowledge obtained a mean value of 6.16 with a standard deviation of 1.04 and nurses’ compliance obtained a mean value of 34.67 with a standard deviation of 3.56. The results of the study concluded that there was no significant correlation between knowledge and nurse compliance in the use of PPE level 2 in Petala Bumi Hospital, Riau Province with p = 0.513 and r = 0.085. Conclusions: This study suggests that nurses increase knowledge and compliance with the use of level 2 PPE in providing nursing services by attending training, seminars and workshops on preventing disease transmission, especially during the COVID-19 pandemic.